Pengaruh pH Terhadap Bentuk Partikel Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Kulit Telur Itik Melalui Metode Presipitasi - M. Gherald Erlangga Putra; Yelmida A; Evelyn Evelyn (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hydroxyapatite (Ca10(PO4)6(OH)2) is the most stable form of calcium phosphate, which is widely used in various medical applications, mainly in orthopedics and dentistry due to it’s similarities with inorganic mineral component of bone and teeth. However, in spite of chemical similarities, mechanical performance of synthetic hydroxyapatite was very poor compared with that of natural bone. It is possible to improve the properties of hydroxyapatite ceramics by controlling important parameters of powder precursors such as particle size, particle shape and agglomeration. In this study, synthesized of hydroxyapatite used PCC and (NH4)2PO4 as raw material. The PCC was made from duck’s eggshells with carbonation method. The hydroxyapatite later would be sintered in 500 ̊C and then characterized by SEM and XRD. The synthesis of hydroxyapatite in this study had been done succesfully with the aid of precipitation method, by controlling the pH. Needle-like hydroxyapatite was synthesized at pH 8 and pH 10 and spherical-like hydroxyapatite was synthesized at pH 12. XRD analysis showed the similarities with standard hydroxyapatite ICDD 01-074-0566. It has been found that the degree of crystallinity had been raised as the pH increased. Keywords: agglomeration, duck eggshells, hydroxyapatite, precipitation